Comparative Study of Alcoholic Extracts of Different Syrian Grapevine and Olive Leaf Cultivars for Their Antioxidant Activity and Photoprotective Effects - Farah Alhakim; Antoun Laham; Jameela Hasian (Advances in Pharmacological and Pharmaceutical Sciences)
A safer alternative made of plant extracts is needed, as evidenced by the negative effects of using synthetic sunscreen. Antioxidant properties of plants with high phenolic content have been reported. The goal of this research was to ascertain the phenolic content and antioxidant characteristics of ethanolic extracts made from grape and olive leaves under various extraction settings. The extracts were subjected to both qualitative and quantitative analyses using HPLC. Soxhlet extraction with 80% ethanol (v/v) as the solvent produced a result that was satisfactory. Four components of grape leaf extract and one component of olive leaf extract were identified. Expressed as gallic acid equivalents (GAEs), the total phenolic content (TPC) of the samples, as determined by using the Folin–Ciocalteu’s reagent, ranged from 38.39 to 72.78 mg/g dry extract of olive and 65.918–132.7 mg/g dry extract of grape. An ethanolic extract of Salmoni (grape leaves) had the highest TPC (132 mg GAE/g), while an ethanolic extract of Zaity (olive leaves) had the lowest (72.66 ± 0.46 GAE/g). The Folin–Ciocalteu method proved the existence of antioxidants in the plant. By scavenging free radicals such as DPPH (2,2-diphenyl-1-picrylhydrazyl), the antioxidant capacity of the plant extracts was determined. Next, the ethanolic extracts of various cultivars of grape and olive leaves were analyzed to determine their sun protection factor (SPF) value. It was 28.8 and 29.96 for grape leaf extract and olive leaf extract, respectively.